THE ROLE OF MODERN COMPUTER TECHNOLOGIES IN THE DIAGNOSIS AND TREATMENT OF GYNECOLOGICAL DISEASES - Atahanov Sanjarbek Anvarovich; Abdullayeva Oysanamxon Khayrulla qizi (Bright Mind Publishing, 2025)
This scientific article analyzes the role and significance of modern computer technologies in improving the effectiveness of treatment processes in gynecology. Technological innovations significantly enhance diagnostic accuracy, minimize invasive treatment, and accelerate the patient’s recovery process
Keywords: Computed Tomography (CT), Magnetic Resonance Imaging (MRI), Robotic Surgery, Gynecology, Diagnostics, Artificial Intelligence (AI).